Paromomycin targets HDAC1-mediated SUMOylation and IGF1R translocation in glioblastoma - Min, Zhong; Guo, Yuejie; Ning, Luo (Frontiers in Pharmacology, 2024)
Objective: This study investigates the effects of Paromomycin on SUMOylationrelated pathways in glioblastoma (GBM), specifically targeting HDAC1 inhibition. Methods: Using TCGA and GTEx datasets, we identified SUMOylation-related genes associated with GBM prognosis. Molecular docking analysis suggested Paromomycin as a potential HDAC1 inhibitor. In vitro assays on U-251MG GBM cells were performed to assess Paromomycin's effects on cell viability, SUMOylation gene expression, and IGF1R translocation using CCK8 assays, qRT-PCR, and immunofluorescence. Results: Paromomycin treatment led to a dose-dependent reduction in GBM cell viability, colony formation, and migration. It modulated SUMO1 expression and decreased IGF1R nuclear translocation, an effect reversible by the HDAC1 inhibitor Trochostatin A (TSA), suggesting Paromomycin's involvement in SUMO1-regulated pathways.This study highlights Paromomycin's potential as a therapeutic agent for GBM by targeting HDAC1-mediated SUMOylation pathways and influencing IGF1R translocation, warranting further investigation for its clinical application.